2013
DOI: 10.48084/etasr.361
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Particles Size Ranges to Sand Friction

Abstract: This work studies the correlation between certain physical properties of granular material such as the friction angle and the grain size distribution. In the laboratory, the determination of friction angle requires hard and expensive testing. Prediction of this parameter from the grading curve proves to be very interesting. Direct shear tests were performed on actual marine sand of Tergha (Algeria) and on seventeen different samples arranged from the same sand with various particle size ranges. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…The results show that the peak shear strength increases as particle size increases. Similar results were obtained by Kara et al [23], Alias et al [24]. In high normal stress of 1000 kPa, natural, medium and fine Kenadsa sand have globally, the same behaviour.…”
Section: Kenadsa Sandsupporting
confidence: 89%
See 3 more Smart Citations
“…The results show that the peak shear strength increases as particle size increases. Similar results were obtained by Kara et al [23], Alias et al [24]. In high normal stress of 1000 kPa, natural, medium and fine Kenadsa sand have globally, the same behaviour.…”
Section: Kenadsa Sandsupporting
confidence: 89%
“…In the results obtained by Kara et al [23], it is noted that there is an increase in peak friction angle with the increase of particles size (Figure 20.). They concluded that if we know the size of particles of marine sand we can deduce directly the value of peak friction angle.…”
Section: Figure 20 Comparison Between Peak Friction Anglesmentioning
confidence: 76%
See 2 more Smart Citations
“…Additionally, according to references [14] and [15], it was concluded that a higher ratio of curvature coefficient to uniformity coefficient (Cc/Cu) results in lower cohesion and internal angle of friction, and the larger the particle size, the higher the internal angle of friction. In contrast, the sand has no cohesion and hardly become denser.…”
Section: Sieve Analysismentioning
confidence: 99%